The Influence of Work-life Balance & Healthy Lifestyle on Mental Health through Focus on Work in Gen Z Employees - Hidayat, Raden Muhamad Daffa; Linando, Jaya Addin (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2024)
The purpose of this study is to find out how a healthy lifestyle and work-life balance impact the mental health of generation Z members. In addition, another objective of this study was to find out how focus on work serves as an intervention factor. This study used quantitative methods, with data collection through questionnaires distributed to 200 Gen Z employees. This data was analyzed using AMOS and Structural Equation Modeling (SEM). The results showed that Gen Z people have better mental health if they have work-life balance and a healthy lifestyle. In addition, focus on work was shown to serve as a link between work-life balance and mental health. These results provide companies with important insights on how to create a work environment that supports a balance between healthy lifestyle and work life to improve employees' mental health.